PENANGGULANGAN GAKY MELALUI PENINGKATAN KUALITAS PRODUKSI DAN DISTRIBUSI GARAM BERYODIUM - Sudarto, Sudarto (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2012)
Nationally, there are approximately 14% of people who do not consume iodized salt which has the effect on health and human intelligence so as to have an important impact on the quality of human resources of a country and impede the rate of HDI (Human Development Index). IDD effective countermeasures can be taken through the coverage of iodized salt consumption by increasing the production and distribution of iodized salt. Methods to achieve accelerated coverage of iodized salt consumption in the community is doing salt iodized in the center of people's salt, iodized salt quality monitoring in small, medium and large industries. In addition, the equitable distribution of iodized salt into the country through isolates areas.